JAVANESE EPISTEMOLOGY REVISITED - Sugiharto, Bambang (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2008)
For the Javanese the whole life is a manifestation of the Absolute.Therefore it is not possible to separate the sacred from the profane,neither morality from religiosity, nor epistemology from ethics.Knowledge, as the pursuit of the truth, is not viewed as in empiricaltradition in which the mind perceives objects out there through thecreation of representations of them by the nervous systems andregistered by the brain (Representationalism); neither as inCartesian intellectualism in which knowledge is founded onindubitable certainties (Foundationalism). It is, instead, a matter ofdoing and venturing (Laku) in which one is to go deeper: fromgross physical body, through subtle body, to the sublime soul. Thecentre of gravity of this pursuit is rasa ( inner feeling, ultimatesecret, the bearer of the divine life, the vehicle of life). Rasa is thequintessence of all the three parts of human structure : the head,the chest and the genital ( the scrotum).